Enhancement of the oral bioavailability of isopropoxy benzene guanidine though complexation with hydroxypropyl-β-cyclodextrin. (31st December 2022) - Lu, Yixing; Yang, Liuye; Zhang, Wanying; Xie, Shiting; Zhao, Feifei; Peng, Xianfeng; Qin, Zonghua; Zeng, Dongping; Zeng, Zhenling
Abstract: Isopropoxy benzene guanidine (IBG) is a novel substituted benzene guanidine analogue with antibacterial activity against multidrug-resistant bacteria. However, the bioavailability of IBG is not optimal due to its finite aqueous solubility, thus hampering its potential therapeutic exploitation. In this study, we prepared IBG/hydroxypropyl-β-CD (IBG/HP-β-CD) complex, and characterized it by differential scanning calorimetry, Fourier transform infrared spectroscopy, powder X-ray diffraction, and scanning electron microscopy. Physicochemical characterization indicated that the crystal morphology of IBG transformed into an amorphous state, thus forming IBG/HP-β-CD inclusion complexes. Complexation with HP-β-CD significantly improve the aqueous solubility, pharmaceutical properties, absorption, and bioavailability of IBG.